INSIGHT INTO EXTRACELLULAR POLYMERIC SUBSTANCES EPS EXTRACTION AND QUANTIFICATION TECHNIQUES: CAUSES, MECHANISMS, AND APPLICATIONS MINI REVIEW - Hadidi, Luna Al (International Journal of Research -GRANTHAALAYAH, 2022)
Microorganisms have a secret world, which is full of baffling phenomena. Without studying this world, we cannot understand the concept of biofilm formation, which is based on the aggregation of different kinds of microorganisms to create micro-colonies. The mysterious world of biofilm is fairly understood. Due to the sophisticated complexity of its structure and architecture, biofilm has many essential properties which had made it an important study field for many researchers in different aspects; public health, water treatment, and especially microbiology. By going into the complexity of biofilm structure, studying Extracellular Polymeric Substances (EPS) for the last decade has provided researchers with great evidence regarding biofilm formation. EPS extraction is the first step toward being able to study the composition and properties of various microbial communities. This review covers EPS extraction techniques and their significant in life.